Proyecto de intervención educativa el covid-19 y su incidencia en la enseñanza básica de los niños de la Escuela Unidocente Carlos María de la Condamine del cantón Chillanes, provincia Bolívar. Año lectivo 2020-2021. - Coloma Ramirez, Katerine Karolina (2021)
The present intervention project called covid-19 and its impact on the basic education of children from the "Carlos María de la Condamine" single-teacher school in the Chillanes canton, Bolívar province. 2020-2021 school year, by analyzing the impact of Covid 19 on children's learning. The Covid 19 pandemic has had a huge impact on education with the closure of schools in almost all parts of the world, due to the fact that most educational centers have been forced to close, adding this to a significant economic recession at the level of all production sectors, which causes greater interruption in learning, malnutrition, domestic violence, inequality and other factors that limit the future of children in what represents the most important simultaneous crisis that all the children have suffered. educational systems of the world. Students from single-teacher schools were the most affected by the closure of face-to-face activities because they do not have internet, advanced telephones and computers, for this reason the children do not have classes virtually but only work with the pedagogical cards. For the intervention project we have 17 students and 1 teacher, through an analysis of Covid 19 in teaching-learning through a survey and interview. In this project we have helped the children of the Carlos María de la Condamine school, solving concerns about the pedagogical cards and school texts in order that the children learn in a better way and facilitate the work of the teacher and parents.